OBJECTIVES, FUNCTION, AND TEACHING MATERIAL OF INDONESIAN LITERATURE IN CURRICULUM KTSP AND K13 AT SMA LEVEL - Triono, Eko; Suwandi, Sarwiji; Andayani, Andayani (Jurnal Pendidikan Bahasa dan Sastra, 2019)
In its teaching, literature undergoes a change in approach along with curriculum changes. This study aims to 1) describe the purpose of teaching literature in curriculum KTSP and K13 at the level of high school; 2) to describe the function of literary teaching in the curriculum of KTSP and K13 in SMA; and 3) to describe the literary teaching materials in the curriculum of KTSP and K13 at SMA level. This research is qualitative descriptive type. The research data is obtained from document archive, informant, and textbook of Indonesian KTSP and K13. Data validity is done by triangulation method and data triangulation. Data collection techniques are content analysis and structured interviews. Data were analyzed interactively. The results of this research are the purpose of teaching literature in KTSP and K13 at SMA level is that students are able to analyze and create literary works, as well as develop individual and social character through literary works. The function of literary teaching in KTSP and K13 is to make literary works as a means of achieving language skills. Third, the literary teaching materials in KTSP and K13 are short stories, poems, plays, novels, reviews.